Ensino de matemática: contribuições das tecnologias digitais e das atividades práticas - Rossatto, Scheila Andretta (2020)
The present work shows the results of a dissertation from the Post Graduation Program Stricto Sensu– Masters Degree in Education by Universidade Federal da Fronteira Sul, Campus Erechim, entitled Mathematics Teaching: contributions from digital technologies and practical activities. The main objective was to investigate in which ways digital technologies and practical activities can promote meaningful learning about mathematical concepts in the ninth year of Fundamental Education through the creation of learning environments involving practical activities and digital technologies. This qualitative research was developed with 9th-grade Elementary School students from a private school in the municipality of Erechim, in the state of Rio Grande do Sul. It has also explored and related trigonometry of right triangles in problem-situations from everyday life, making use of practical activities. The students involved realized activities of exploration of the 1st and 2nd-degree functions with the GeoGebra software, identifying and recognizing the importance of Mathematics in daily life. From the notes of the researcher’s logbook, transcriptions from classes’ recordings, and considerations on the report written by the students it was analyzed the process of construction of mathematical concepts, aiming to identify the potentialities, the difficulties, and the different mathematical constructions created, as well as the manifestations of meaningful learning from the students. The work was based on Ausubel’s Meaningful Learning Theory (1982 and 2003) and utilized the content analysis proposed by Bardin (1977) to reflect critically on the empirical material. Thinking Mathematics allied to digital technologies and practical activities of the 9th grade from Elementary School represents one of the researcher’s concerns, considering the challenges and the difficulties already observed in recurrent empirical experiences in the classroom. In general, technological resources have not been used in the teaching and learning processes in the school environment; such aspect is reinforced by the lack of technological formation of teachers, and by the predominant school culture, in which there is an emphasis in the expositive approach to knowledge. Subjects involved in the process of learning search for a school that is connected to what they know or have contact with, but sometimes schools1 seem not to be open to what is new. The manifested resistance in the school environment mainly emerges due to factors as lack of financial investments, lack of will from those who should give subsidies to offer quality education, as well as teacher’s unpreparedness to deal with the new; in particular with the insertion of digital technologies in the processes of teaching and learning. We hope that this work may contribute to other teachers so that they start to incorporate digital technologies and practical activities in their pedagogical practices.